2014
DOI: 10.1155/2014/286013
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a Tongue Squamous Cell Carcinoma Cell Line from Indian Gutka Chewer

Abstract: CD cell line has been established from a poorly differentiated squamous cell carcinoma of tongue. This is a first ever cell line established from an Indian gutka chewer. Cell line was characterized for morphology, ultrastructure, doubling time, expression of epithelial markers, DNA content, karyotyping, STR markers, p53 mutations, HPV status, and tumorigenicity in SCID mice with all-trans-retinoic acid and cisplatin. The epithelial phenotype of the cell line was confirmed with surface markers and ultrastructur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…Human tissue sampling was approved by the Changhua Christian Hospital Institutional Review Board and written informed consent from the patients. The normal oral epithelial cells were isolated and cultured as described previously by Patil et al [28]. The tissues were cut into smaller pieces and incubated with trypsin (0.025%) for 30 min, at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…Human tissue sampling was approved by the Changhua Christian Hospital Institutional Review Board and written informed consent from the patients. The normal oral epithelial cells were isolated and cultured as described previously by Patil et al [28]. The tissues were cut into smaller pieces and incubated with trypsin (0.025%) for 30 min, at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, cell lines are required for evaluating the effects of numerous novel drugs and finding better treatments (Kaur and Ralhan, 2003). Several studies identified that the wide variety of patients who suffered from tongue cancer were smokers and most cell lines were determined from them, whereas few cell lines recognized from tumors of nonsmokers (Patil et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The establishment of HNSCC cell lines from Indian patients has previously been achieved from carcinomas of tongue, alveolus and retromolar trigone (24,25); however, these cell lines did not possess the ability to give rise to tumors when injected into immune-compromised mice (24,25). Furthermore, the establishment of a cell line from carcinoma of the upper aerodigestive tract, which can give rise to tumors when subcutaneously xenografted in nude mice was reported (26).…”
Section: Establishment and Characterization Of Novel Human Oral Squamous Cell Carcinoma Cell Lines From Advanced-stage Tumors Of Buccal Mmentioning
confidence: 99%